Negotiations of Science and Religion in Nordic Institutions: An Ethnographic Approach - Tiaynen-Qadir, Tatiana (Religions, 2021)
This article explores how two seemingly contradictory global trends—scientific rationality and religious expressiveness—intersect and are negotiated in people’s lives in Nordic countries. We focus on Finland and Sweden, both countries with reputations of being highly secular and modernized welfare states. The article draws on our multi-sited ethnography in Finland and Sweden, including interviews with health practitioners, academics, and students identifying as Lutheran, Orthodox, Muslim, or anthroposophic. Building on new institutionalist World Society Theory, the article asks whether individuals perceive any conflict at the intersection of “science” and “religion”, and how they negotiate such a relationship while working or studying in universities and health clinics, prime sites of global secularism and scientific rationality. Our findings attest to people’s creative artistry while managing their religious identifications in a secular, Nordic, organizational culture in which religion is often constructed as old-fashioned or irrelevant. We identify and discuss three widespread modes of negotiation by which people discursively manage and account for the relationship between science and religion in their working space: segregation, estrangement, and incorporation. Such surprising similarities point to the effects of global institutionalized secularism and scientific rationality that shape the negotiation of people’s religious and spiritual identities, while also illustrating how local context must be factored into future, empirical research on discourses of science and religion.